Psychological distress in cancer patients after laryngectomy - G. A. Tkachenko; S. О. Podvyaznikov; А. M. Mudunov; О. A. Obukhova; A. A. Akhundov; М. М. Khulamkhanova; E. I. Skvortsova (Опухоли головы и шеи, 2019)
The study objective is to analyze mental state of patients with laryngeal cancer after laryngectomy.Materials and methods. The study included 38 patients at various stages of laryngeal cancer treatment. To assess mental state, we used the Hospital Anxiety and Depression Scale (HADS) and the Symptom Checklist-90-R (SCL-90-R).Results. In general, preoperative mental state of study participants was close to that in healthy individuals (described in literature), although there was a slight increase in their levels of depression and anxiety and higher distress severity indices. Six months after laryngectomy, a high level of distress was found; all patients had higher scores in all primary symptom dimensions; however, a significant increase was registered only for anxiety, depression, somatization, hostility, and interpersonal sensitivity. Six months postoperatively, mean anxiety score reduced, but was still higher than preoperative one and normal one. There was a significant increase in depression score and interpersonal sensitivity score. Conclusion. Our findings suggest the need for special programs of psychological rehabilitation for patients with laryngeal cancer to teach them the skills needed for self-regulation of mental state in order to increase their stress resistance.